If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -3i = x + 12yi Reorder the terms: 4 + -3i = 12iy + x Solving 4 + -3i = 12iy + x Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-12iy' to each side of the equation. 4 + -3i + -12iy = 12iy + -12iy + x Combine like terms: 12iy + -12iy = 0 4 + -3i + -12iy = 0 + x 4 + -3i + -12iy = x Add '-4' to each side of the equation. 4 + -3i + -4 + -12iy = -4 + x Reorder the terms: 4 + -4 + -3i + -12iy = -4 + x Combine like terms: 4 + -4 = 0 0 + -3i + -12iy = -4 + x -3i + -12iy = -4 + x Reorder the terms: 4 + -3i + -12iy + -1x = -4 + x + 4 + -1x Reorder the terms: 4 + -3i + -12iy + -1x = -4 + 4 + x + -1x Combine like terms: -4 + 4 = 0 4 + -3i + -12iy + -1x = 0 + x + -1x 4 + -3i + -12iy + -1x = x + -1x Combine like terms: x + -1x = 0 4 + -3i + -12iy + -1x = 0 The solution to this equation could not be determined.
| 7x-4y+8.04-2.7x=5y-0.8x+2 | | 3(2x-15)=4(x+1) | | 3(2x-15)=4(4x+1) | | 2x+y-x+4yi=-1+13i | | 3(2x-15)=4(4+1) | | 5x+3yi=15+i | | 15+-3i+3iy+2x+5y=0 | | y^3-y^2+2y-2=0 | | 7x+456=23x(762-500)+76(8x+25) | | 3x+756=6x+76 | | 8+m=48 | | 21+n=31 | | 36x+2-66=49+56-9 | | x-6=66+8 | | 2x+y+2=0 | | 5w^2-w+2=0 | | x^2-10x+16=-3 | | 2-5h=-18 | | 3(6z-1)-4z+-8=6z+7 | | x(356)1= | | 65775+57755= | | 191-2x=43x+16 | | -(z+6)+(4z+1)=-1z+1 | | 8-9x=70-23x | | -6(t-7)-(t+5)=3 | | s(s-5)=14 | | 7x+9x=3+9x | | B=GN | | 34x+6=8 | | 3a-3=11 | | x^2+20x-6000=0 | | x^2+20x+6000=0 |